A Study to Analyze Collaboration Patterns for Asian Library and Information Science (LIS) Scholars on Author, Institutional and Country Levels. Issue 1 (2nd January 2016) - Jabeen, Munazza; Yun, Liu; Wang, Xuefeng; Rafiq, Muhammad; Mazher, Abeer; Tahir, Muhammad Azam; Jabeen, Misbah
ABSTRACT: The aim of the present study is to determine the collaborative activities of Asian library and information science (LIS) researchers through bibliometric, social network analysis at the author, institution, and country levels of the LIS publications produced by Asian researchers. For the study, research articles were derived from the 1994–2013 Web of Science (WoS) archives. Coauthor analysis software was used to analyze author contributions on the New Modified Author Activity Index (NMAAI1, 2, 3 )—a measurement tool to evaluate author research activities. Results reveal (a) that LIS "institutions collaboration pattern" outcomes did not yield strong collaboration with Asian countries or regions, (b) intracontinent and intercontinent collaboration was less harmonious on institutional and author levels, and (c) interpretation through NMAAI1, 2, 3 revealed that Asian countries did not produce sufficient collaborative LIS publications. Taiwan, South Korea, Singapore, India, Iran, Israel, and Turkey have been producing ample LIS papers, but the United States and United Kingdom emerged as leaders. This work provides a holistic view of Asian LIS development and emphasizes individual levels of collaboration, finding that most influential authors serve on coauthor networks, which differentiates this study from previous studies in the LIS field. There is immense need to develop liaisons, sign memoranda of understanding (MOUs), and participate in combined research plans and short-term research exchange programs.